The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1371/journal.pone.0265341
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and generational determinants of Poles’ participation in the sharing economy: Findings from a survey data analysis

Abstract: The fast development of technologies in today’s world is accompanied by the mushrooming of digital platforms constituting the core of the ecosystem of sharing economy. This multifaceted phenomenon and its ever-increasing presence have become a subject of public interest and debate, as well as encouraging research and scientific discourse. The article presents the results of the first study of Poles’ participation in sharing economy derived from a questionnaire survey of a representative sample (n = 1000). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The research conducted in Indonesia exposed that the interest of young people in utilizing or choosing digital financial platforms, one of which is crowdfunding platforms, occurs as the impact of digital financial literacy gets more robust in the younger generation. This phenomenon is also demonstrated by the research of Warwas et al (2022), showing that young people's ability to adapt to technology quickly is the key to their involvement in digital finance in Poland, which represents the situation in Europe. The phenomenon shown by previous research denotes the profound influence of young people on the development of digital finance.…”
Section: Young People and Digital Financementioning
confidence: 81%
See 1 more Smart Citation
“…The research conducted in Indonesia exposed that the interest of young people in utilizing or choosing digital financial platforms, one of which is crowdfunding platforms, occurs as the impact of digital financial literacy gets more robust in the younger generation. This phenomenon is also demonstrated by the research of Warwas et al (2022), showing that young people's ability to adapt to technology quickly is the key to their involvement in digital finance in Poland, which represents the situation in Europe. The phenomenon shown by previous research denotes the profound influence of young people on the development of digital finance.…”
Section: Young People and Digital Financementioning
confidence: 81%
“…To give a novelty to previous research, this current study involved young people respondents to assess what factors made them interested in contributing to crowdfunding platforms. Previous research did not specifically show how young people might be attracted to contribute to crowdfunding platforms, although research by Bhardwaj et al (2019), Arifah andDalimunthe (2021), andWarwas et al (2022) have shown the phenomenon of high youth involvement in digital finance, including crowdfunding. By identifying the dominant factors attracting young people, the success factors of crowdfunding platforms can be prepared for the future.…”
Section: Hariwibowomentioning
confidence: 99%
“…According to statistics from Statista (2021), nearly 45 million adults in the US used SE services, rising to nearly 87 million by 2021. Study of Warwas et al (2022) demonstrates that among the most popular platforms are accommodation booking services (26.7%), which are mainly used by Poles aged 25-34 (44%) and 18-24 years old(39%). Less frequently used services include the free exchange of goods, services, knowledge and skills (17%).…”
Section: Literature Reviewmentioning
confidence: 99%